Power Engineering and Intelligent Systems Proceedings of PEIS 2024, Volume 2 - Shrivastava, Vivek; Bansal, Jagdish Chand; Panigrahi, B. K. (Lecture Notes in Electrical Engineering, 2024)
XVI, 535 p. 275 illus., 243 illus. in color.